The Effect of Competency and Locus of Control on Personal Quality of Managers in the South Sumatera Province - Indonesia - Soebyakto, Bambang Bemby (2009)
The perception of IQ, emotional quotient (EQ), and spiritual quotient (SQ) have been predicted to escalate with the increase of personal quality (PQ) of corporate managers. In line with the enhancement of personal quality, internal locus of control has been estimated to amplify the three entities. Therefore, this study is intended to investigate the drives of personal quality of corporate managers based on the examination of intelligence, emotional, and spiritual quotients (IESQ) and mediated by internal locus of control. The data were collected from 255 corporate managers in Indonesia via questionnaires. The analysis produced structural models of personal quality predicted by IESQ and mediated by internal LOC. The results of the study indicated that the hypothesized model has shown that there is a significant correlation between positive direct (IESQ) and indirect (internal LOC) impacts of predictors and personal quality of managers. For mediating effect of internal LOC on each hypothesized path, the study found partial mediating effects of internal LOC. Finally, the structural model achieved the highest SMC(R2), explaining 60.1 % variance in the personal quality of managers. All hypotheses of this study confirmed that there is a positive direct relationship between IESQ and PQ.